MIS, 10th Edition - Hossein Bidgoli (Cengage Learning, 2020)
Introduce your students to MIS today with the most practical and current title available: MIS 10. Updates throughout this edition present the latest developments in cloud computing, AR/VR, quantum computing and blockchain. New case studies and information boxes connect the principles your students are learning to the most current developments in technology and business today. Key concepts and skills within each case are now tagged to the corresponding AASCB standards to ensure your students are focused on the most important information for success.